2019
DOI: 10.3892/ol.2019.11013
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the early stage gene expression profiles of lung adenocarcinoma and lung squamous cell carcinoma

Abstract: The discovery of lung carcinoma subtype-specific gene expression changes has the potential to elucidate the molecular differences and provide personalized therapeutic targets for these pathologies. The aim of the present study was to characterize the genetic profiles of the early stages (IA/IB) of two non-small cell lung cancer subtypes, adenocarcinoma (AD) and squamous cell carcinoma (SC). RNA-Seq gene expression data from The Cancer Genome Atlas was analyzed to compare the gene expression differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
1
3
2
Order By: Relevance
“…In SCC we could confirm apolipoprotein 1 (APOA1) which has previously been described as inversely correlated with the risk of lung cancer 26 . Interestingly, the paper by Venugopal et al 23 showed fibrinogen alpha (FGA) to be overexpressed in ADC, in our dataset, however, it was found with higher expression levels in SCC. In addition, we were able to quantify several proteins that might be of interest as potential future markers for lung ADC, such as mucin-5AC (MUC5AC), another mucin that has been linked to ALK-positive lung ADC 27 , or carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6), a glycoprotein that is involved in cell invasion and metastasis and has been shown to have higher expression levels in ADC compared to SCC via IHC 28 .…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…In SCC we could confirm apolipoprotein 1 (APOA1) which has previously been described as inversely correlated with the risk of lung cancer 26 . Interestingly, the paper by Venugopal et al 23 showed fibrinogen alpha (FGA) to be overexpressed in ADC, in our dataset, however, it was found with higher expression levels in SCC. In addition, we were able to quantify several proteins that might be of interest as potential future markers for lung ADC, such as mucin-5AC (MUC5AC), another mucin that has been linked to ALK-positive lung ADC 27 , or carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6), a glycoprotein that is involved in cell invasion and metastasis and has been shown to have higher expression levels in ADC compared to SCC via IHC 28 .…”
Section: Resultscontrasting
confidence: 65%
“…2A ). With this dataset, we could confirm several markers on a protein level that had previously been shown on RNA level 23 , such as mucin-5B (MUC5B), a glycoprotein that is secreted in the lung and is associated with poor prognosis in ADC 24 , kininogen 1 (KNG1), and serum transthyretin (TTR), which has been shown to be associated with poor outcome 25 . In SCC we could confirm apolipoprotein 1 (APOA1) which has previously been described as inversely correlated with the risk of lung cancer 26 .…”
Section: Resultssupporting
confidence: 55%
“…In SCC we could confirm apolipoprotein 1 (APOA1) which has previously been described as inversely correlated with the risk of lung cancer 26 . Interestingly, the paper by Venugopal et al 23 showed fibrinogen alpha (FGA) to be overexpressed in ADC, in our dataset, however, it was found with higher expression levels in SCC. In addition, we were able to quantify several proteins that might be of interest as potential future markers for lung ADC, such as mucin-5AC (MUC5AC), another mucin that has been linked to ALK-positive lung ADC 27 , or carcinoembryonic antigen-related cell adhesion molecule 6 (CEA-CAM6), a glycoprotein that is involved in cell invasion and metastasis and has been shown to have higher expression levels in ADC compared to SCC via IHC 28 .…”
Section: Resultscontrasting
confidence: 65%
“…However, the results of this experiment show that the effect of ACBP is different at the protein level compared with the mRNA level, and further research on the relevant signaling process is needed. GES-1 is a tumorigenic [12], immortalized human gastric mucosal epithelial cell line, and Lin28 is highly expressed in growing and developing GES-1 cells; it exhibits high expression in multiple tumor cell lines [33] and comparatively low expression in human gastric mucosal cells. The results of this study indicated that OXA, ACBP and the combination downregulated Lin28 gene expression, but the Lin28 protein expression level was not measured in GES-1 cells due to its low expression in these cells.…”
Section: Discussionmentioning
confidence: 99%